TEKTONIKA LUMBUNG (LANDA’) RUMAH TRADISIONAL DURI DI KABUPATEN ENREKANG - AS, Zulkarnain; Ahmad, Ibrahim Rahmani (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Landa 'is the name for the granary of the Duri Tribe, which is different from the barns in the archipelago and is full of architectural metaphysical values. Landa's existence in Enrekang District was founded in three villages, one of which is Kendenan Village, which is the location of the study because the most significant number of Landa is in this village. The community still holds the traditions inherited from their ancestors. This research aims to uncover and discover the characteristics of the structure and construction of the terrace'. The research method used a qualitative approach with descriptive analysis techniques. The research results reveal that vertically the Landa 'is divided into three main parts. the first leg/bottom (Bala Landa') uses the column frame structure system, and the construction uses the fulcrum and perforation system; the second part is the body/middle (Kale Landa). ) which uses a siamma structure and construction system, and the third part of the head/top (Dea Landa ') uses a beam frame and a construction system using a stack, notch, and perforation system. Knowledge and the design process of Landa 'are full of local wisdom values responsive to disasters.